Multicultural-Based Islamic Education As The Foundation To Reduce Attitudes Of Religious Radicalism - Oktori, Agus Riyan (AJIS: Academic Journal of Islamic Studies, 2017)
The widespread of violence cases in the name of religion are so frequent in Indonesia which need to get attention, especially by Islamic educational institutions. Islamic teachings that have always upheld the diversity, human values, love of peace, and amatory began to fade away by an exclusive religious understanding by a group which is called radicals. Various conflicts that occur should immediately find a solution to not expand and sustainable. Multicultural-based Islamic education is one of the alternative ways that can be the foundation to reduce the attitude of radicalism. The content of multicultural values that can be internalized among others is the value of tolerance, the value of democracy, and the value of peace.